Hubungan Implementasi Protokol Pencegahan Infeksi Nosokomial dengan Angka Infeksi pada Pasien ICU di RSI Sultan Hadlirin Jepara - Muhamad Zamroni; Ratna Ratna; Akbar Amin Abdullah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Nosocomial infections are a major challenge in healthcare, particularly in intensive care units (ICUs). Although the incidence in ICUs is not particularly high, they still occur. Adherence to hygiene protocols has been shown to reduce infection rates by up to 30%. Data from the Indonesian Ministry of Health (2020) indicates that nosocomial infections in hospitals account for 20–30% of all ICU patients. Objective: To determine the relationship between the implementation of nosocomial infection prevention protocols and infection rates in ICU patients at Sultan Hadlirin Islamic Hospital (RSI) in Jepara. Methods: This study was quantitative with a correlational cross-sectional design. The population included all 10 healthcare workers in the ICU and 23 admitted patients. The sampling technique used was total sampling. The research instruments were questionnaires and observation sheets, while data analysis was performed using the Chi-square test. Results: A total of 17 patients were treated with the prevention protocols in place, but one patient still experienced a nosocomial infection. The test results showed an asymptotic significance value (2-sided) of 0.59 > 0.05. Conclusion: There is no influence of the implementation of infection prevention protocols on the incidence of nosocomial infections (INOS) in the ICU at RSI Sultan Hadlirin Jepara.